2021
DOI: 10.1186/s12968-021-00766-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high risk clinical and imaging features for intracranial artery dissection using high-resolution cardiovascular magnetic resonance

Abstract: Background Intracranial artery dissection (IAD) often causes headache and cerebral vascular ischemic events. The imaging characteristics of IAD remain unclear. This study aims to characterize the appearance of culprit and non-culprit IAD using high-resolution cardiovascular magnetic resonance imaging (hrCMR) and quantify the incremental value of hrCMR in identifying higher risk lesions. Methods Imaging data from patients who underwent intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Since an ischemic event caused by a culprit dissection might seriously affect the prognosis of an IAD patient, finding predictive factors is of great significance. It was suggested in a previous study that hypertension was a key factor for vertebral artery dissection [35]. In accordance with previous studies, a remarkable difference was found here in the percentage of patients with hypertension, together with double lumen and intimal flap between culprit and non-culprit.…”
Section: Discussionsupporting
confidence: 92%
“…Since an ischemic event caused by a culprit dissection might seriously affect the prognosis of an IAD patient, finding predictive factors is of great significance. It was suggested in a previous study that hypertension was a key factor for vertebral artery dissection [35]. In accordance with previous studies, a remarkable difference was found here in the percentage of patients with hypertension, together with double lumen and intimal flap between culprit and non-culprit.…”
Section: Discussionsupporting
confidence: 92%
“…The smaller diameters of these arteries limit the ability of routine vascular imaging examinations to detect characteristic imaging features of dissection, including true and false lumen and intimal flap; the dissection tends to be missed or misdiagnosed as aneurysm, vasculitis, or fibromuscular dysplasia, etc. (32,33).…”
Section: Intracranial Arterial Dissectionmentioning
confidence: 99%
“…It could demonstrate the distinguishing morphological features of the chronic stage of spontaneous and unruptured IAD as complete normalization, complete normalization with minimal wall changes, incomplete normalization, dissecting aneurysm, and occlusion ( 13 ). It provided a significant complementary value over DSA for the diagnosis of IAD ( 14 ). In predicting IAD changes, quantitative analysis of contrast enhancement on magnetic resonance vessel wall imaging (MR–VWI) could predict the instability of unruptured IAD ( 15 ).…”
Section: Discussionmentioning
confidence: 99%